(untitled) (Palíndromo, 2016)
Having the thesis Museum of Mo- dern Art Department of Eagles, held by Keila Kern at ECA / USP in 2015, as a star- ting point, this article seeks to reflect on the process of writing, make an art work and write a thesis as practices also irre- gular and poetic - writing as un coup de dés, as it defended Mallarmé; write to make ourselves wild, as argued Margue- rite Duras.